Chromosome-level genome assembly of Qihe gibel carp - Kaiqi Lian; Jinyan Shan; Jun Ma; Yuling Liu; Xiaolong Li; Meng Lu; Miao Ding; Jie Wei; Li Zhou; Youyi Kuang; Jianfang Gui; Renhai Peng (Scientific Data)
Abstract Qihe gibel carp (Carassius gibelio var. Qihe) is a local population of natural gynogenetic amphitriploid (AAABBB) Carassius gibelio, and has high nutritional and economic value. In this study, we assemble a high-quality chromosome-level genome of Qihe gibel carp through DNBSEQ, PacBio HiFi, and Hi-C sequencing data. The resulting assembly consisted of 350 contigs with the full length of 1.607 Gb and 96.21% (1.515 Gb) of the assembled genome was successfully anchored to 50 chromosomes, with a contig N50 of 28.97 Mb and a scaffold N50 of 29.84 Mb. Repeated sequences accounting for 43.72% (732.494 Mb) of the total were also identified, and gene prediction revealed 46,131 protein-coding genes with an annotation ratio of 96.48%. Furthermore, Benchmarking Universal Single-Copy Orthologue (BUSCO) analysis demonstrated that the genome assembly achieved high completeness, with a score of 97.66%. This high-quality chromosome-level genome lays the foundation for molecular biology research as well as molecular breeding and evolutionary studies of Qihe gibel carp in the future.